Dansk bogfortegnelse. - Føroya landsbókasavn.; Kongelige Bibliotek (Denmark); Dansk bibliografisk kontor.; Folkebibliotekernes bibliografiske kontor (Denmark); Bibliotekscentralen (Denmark)
Annual cumulation has subtitle: Årskatalog. Vols. for 1965- include: Færøsk bogfortegnelse; for 1971- include: Grønlandsk bogfortegnelse; for 1972- include: Dansk kortfortegnelse. Vols. for 1915/19-1930/34 include Islandsk bogfortegnelse for the same dates. Annual vols. for 19<50>- called also: <100.>- aarg. Mode of access: Internet. Vols. for 1945/49 compiled by: Folkebibliotekernes Bibliografiske Kontor; for 1950/54-1955/59 by: Dansk Bibliografisk Kontor; for 1960/64- by: Bibliotekscentralen (for 1984- in collaboration with: Det kongelige Bibliotek, and: Føroya Landsbókasavn). After 1981, the weekly, monthly/quarterly and annual lists include data on serials titles, and serve as updates to the latest five-year or ten-year general serials list: Dansk periodicafortegnelse; this data formerly issued as annual cumulated supplements to that title. Cumulated from weekly listings in: Det Danske bogmarked. MAIN; Z2561.D2: Bound holdings include annual volumes until quinquennial cumulations received